Reproductive performance of crossbred dairy cattle in selected urban and peri-urban farms of mid rift valley, Ethiopia - Chalisia, G.; Mekasha, Yoseph; Urge, Mengistu (Academic Journals, 2014)
This study was conducted to evaluate reproductive performance of crossbred cows and to identify potential constraints of dairying under small and medium scale farmers’ management in urban and peri-urban dairying of mid rift valley, Ethiopia. The data was collected through questionnaire from 120 small and medium dairy farm owners. The overall estimated mean age at first service and age at first calving was 20.6±02 and 30.6±0.19 months, respectively, and differed (P<0.01) considerably among production systems and herd size groups. The overall estimated mean lactation length, days open and calving interval were 311.3±2.8 and 128.2±2.4 days and 14.07±0.09 months, respectively, and differed significantly (P<0.01) between production systems and herd size groups. According to the respondents, feed shortage and limitation of space were reported as major constraints of dairy production in urban area, whereas feed cost, shortage of feed and Artificial Insemination (AI) service were major constraints of the peri-urban production system. Therefore, from the current study it was concluded that the reproductive performances of animals on both production systems and farm scale were below their expected genetic potential. Hence, large variation between production systems and farm scale groups showed the opportunities for further improvement with strategic supplementation of energy and protein rich feeds.